Audits for the Use and Strategic Of Energy Efficiency on the Campus Bukit Indah of Malikussaleh University - Hasibuan, Arnawan; Siregar, Widyana Verawaty; Ezwarsyah, Ezwarsyah; Kurniawan, Robi (LPPM Universitas Andalas, 2021)
This study aims to determine the right strategy for energy efficiency that can be applied in the campus area. This study uses quantitative methods in a dominant position, while qualitative methods are less dominant. The method of analysis for this study uses Contextual Interaction Theory (CIT) with the characteristics of the implementer and the target group consisting of motives, cognition, and strengths. These variables will be the main points for formulating a basic strategy on energy use at the Faculty of Engineering, Bukit Indah campus, Malikussaleh University. Contextual issues are also external factors that influence and become a consideration in determining the level of energy efficiency efforts on campus. Regarding to CIT measurements which have been analyzed, the score of motives from implementer is -0.33, cognitions +0.50, and power +62. Then, overall for target group get positive score which consist of motives +0.75, cognitions +0.54, and power +0.44. The result of type interaction between two actors point out number 10 which is about obstructive. Apart from that, three contextual issues will also be analyzed that affect the characteristics of actors, namely the specific context, the structural context and the broader context. Strategic planning to pursue energy efficiency at the Faculty of Engineering, Bukit Indah Campus, Malikussaleh University consists of increasing motivation with energy-saving campaigns and awarding prizes. Then, improve cognition with energy audits and socialization of energy efficiency. Finally, increasing strength through the implementation of sustainable policies and programs.